2010
DOI: 10.1016/j.jasms.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Probing the hydrophobic effect of noncovalent complexes by mass spectrometry

Abstract: The study of noncovalent interactions by mass spectrometry has become an active field of research in recent years. The role of the different noncovalent intermolecular forces is not yet fully understood since they tend to be modulated upon transfer into the gas phase. The hydrophobic effect, which plays a major role in protein folding, adhesion of lipid bilayers, etc., is absent in the gas phase. Here, noncovalent complexes with different types of interaction forces were investigated by mass spectrometry and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
(52 reference statements)
2
62
0
Order By: Relevance
“…Even when carefully controlling the instrument parameters, complexes that are predominatly stabilized by nonpolar interactions are prone to dissociation in the gas phase [25]. This so-called in-source dissociation can lead to an artificially low binding constants based on the reduced abundance of the complex ions [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when carefully controlling the instrument parameters, complexes that are predominatly stabilized by nonpolar interactions are prone to dissociation in the gas phase [25]. This so-called in-source dissociation can lead to an artificially low binding constants based on the reduced abundance of the complex ions [21].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies it was shown that the gas-phase stability reflects the binding properties in solution [37][38][39]. More frequently, however, a correlation between the gas-phase stability and the solution-phase stability is absent [25,26,28,[40][41][42][43][44][45][46], for example for leucine-zippers and acyl-CoA binding protein (ACBP) and a series of acyl CoA derivatives [28]. If binding properties in solution correlate with gas-phase stability it has to be assumed that the dominant interactions are very similar in solution and in the gas phase, and that solvent mediation play only a minor role (see Daniel at al.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been few reports of the application of ESI-MS to directly characterize hydrophobic protein-ligand interactions [23,[83][84][85][86]. In fact, it has been suggested that the direct ESI-MS assay does not give results that accurately reflect the solution equilibria for protein-ligand interactions that are dominated by hydrophobic bonding [87]. The underlying argument is that because hydrophobic bonding requires the presence of water, the dehydrated complexes are unstable in the gas phase [49,88].…”
Section: Future Directionsmentioning
confidence: 99%
“…In another study dealing with the domain interplay of uPAR, the detected amount of cross-linked uPAR-ATF complex exceeded the level predicted from the equilibrium binding situation after 15 min cross-linking reaction at pH 7.4 [26]. In contrast, Bich et al detected complex levels of about 90% of the predicted values on average after chemical cross-linking with the amine reactive homobifunctional cross-linker 1,1=-(suberoyldioxy)bisazabenzotriazole (SBAT) and MALDI-MS detection [27]. The question arises whether the chemical stabilization of the noncovalent complex can disturb the solution phase equilibrium and, if so, under which conditions a shift could be expected.…”
Section: Considerations On the Disturbance Of The Chemical Equilibriummentioning
confidence: 99%